EFEKTIVITAS EKSTRAK DAUN DIWOKA (Piper miniatum Bl.) SEBAGAI PESTISIDA NABATI DALAM MENGENDALIKAN HAMA ULAT TRITIP (Plutella xylostella) PADA TANAMAN KUBIS - Inrianti, Inrianti; Paling, Sepling; Mosip, Erinus; Berliana, Meri; Pian, Hendrik Yulius; Walila, Maktalina (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2024)
This study aims to examine the effect of various concentrations of Diwoka leaf extract (Piper miniatum Bl.) on the mortality of diamondback moth (Plutella xylostella) on cabbage (Brassica oleracea var. capitata L.) in a laboratory scale. Diwoka leaf extract was applied at concentrations of 40%, 50%, 60%, 70%, 80%, and 90%, with the mortality of the diamondback moth observed after five hours. The results showed that the higher the concentration of Diwoka leaf extract, the higher the mortality rate of the diamondback moth. At a concentration of 90%, mortality reached 97.50%, while at 40%, mortality was only 32.50%. These findings indicate that Diwoka leaf extract can function as an effective botanical pesticide in controlling diamondback moth on cabbage plants. This study contributes significantly to the development of alternative natural pesticides that are environmentally friendly and have the potential to be applied in sustainable agriculture.